PHYSICAL PROPERTIES OF BEEF NUGGET WITH THE ADDITION OF DIFFERENT EGG WHITES - Harliani, Wa Ode; Hafid, Harapin; Pagala, Muhammad Amrullah (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
The purpose of this study was to determine the Physical and Organoleptic Properties of Beef Nuggetwith the Addition of Different Egg White Percentages. The research was carried out in 2 stages,namely preliminary research and primary research. The preliminary research aims to determine theprocess of making and formulating the useful nuggets with egg whites. The main research wasconducted to determine the physical and organoleptic beef nuggets by adding a different egg whitepercentage. This research was carried out experimentally using a Completely Randomized Designwith four treatments and five replications in the physical test and 15 semi-trained panelists as a test inthe organoleptic test. Trained panelists were recruited from students and alumni of the Department ofAnimal Husbandry, Faculty of Animal Husbandry, the University of Halu Oleo, who understood thescience and technology of meat and were willing to do an organoleptic perception testing (hedonictest). The form of treatment is adding a white egg percentage on beef nuggets consisting of fourtreatments. The composition of the experiment is as follows: P0 = Giving 0% (0 gram) egg whites and100% beef, P1 = Giving 5% (5 grams) egg whites and 100% beef, P2 = Giving 10% (10 grams) whiteeggs and 100% beef, and P3 = Provision of 15% (15 grams) egg whites and 100% beef. The variablesmeasured in this study include Physical and Organoleptic Properties of Beef Nugget. Physicalvariable tests include pH and yield, while Organoleptic variables test, namely color, aroma, taste,tenderness, and texture. Based on the results and discussion, it can be concluded that adding adifferent percentage of egg white to the nugget does not affect the pH and the rendering of the beefnugget. Meanwhile, based on organoleptic test results (color, aroma, taste, texture, and tenderness),beef nuggets with the addition of a different percentage of egg white affect the texture but does notaffect the color, aroma, taste, and tenderness. It should be continued with the addition of egg whiteswith a higher level, from this study to see the effect on the physical and organoleptic properties ofBeef Nugget.